Analysis of a syndromic surveillance system for infectious diseases of the 31st summer World University Games in Chengdu, China - Yao Wang; Yingxue Dai; Hui Liu; Songqi Feng; Yuezhu Chen; Lu Long; Ke Yan; Xunbo Du; Changhui Du; Liang Wang (Frontiers in Public Health, 2025)
IntroductionChengdu hosted the 31st Summer World University Games in 2023. The movement and gathering of attendees from other cities and countries posed challenges to local public health, including an increased risk of infectious diseases or outbreaks. To manage these risks, a syndromic surveillance system targeting infectious diseases was established. This system aimed to identify suspicious cases and outbreaks early, enabling timely measures and minimizing their impact. This article reviews the surveillance mechanism, analyzes the surveillance data, and evaluates the system’s effectiveness.MethodsThe mechanism of the syndromic surveillance system was described, and surveillance data were collected to evaluate strategies for infectious disease prevention and control during the Universiade. Epidemiological distributions of diseases were described, and differences were tested using chi-squared tests.ResultsSurveillance was carried out among athletes, coaches, entourages, and staff from 1 week before the competition to 1 week after. The surveillance focused on symptoms such as fever, cough, diarrhea, vomiting, rash, jaundice, conjunctival redness, and sore throat, supported by a self-developed Cloud Health Information System for Health Care Support and Syndromic Surveillance System for Infectious Disease. A total of 351 subjects with disease-related symptoms, mainly including sore throat, cough, and fever, were reported. A total of 33 events of clustered symptoms were detected, none of which met the criteria for an outbreak. Fifty cases were confirmed with infectious diseases, comprising 43 cases of COVID-19, 3 cases of influenza, and 1 case each of infectious mononucleosis, chikungunya, malaria, and another infectious diarrhea.DiscussionThroughout the event, reports of disease-related symptoms were sporadically distributed, with no secondary cases or outbreaks detected and no health-related risks arising that would impact the continuation of the event. The syndromic surveillance system was sensitive and effective for the early detection and control of infectious disease outbreaks and could be implemented in other mass-gathering events.